Beyond outrage what has gone wrong with our economy and our democracy and how to fix it - Reich, Robert B. (New York Vintage Books, 2012)
America?s economy and democracy are working for the benefit of an ever-fewer privileged and powerful people. But rather than just complain about it or give up on the system, we must join together and make it work for all of us.